Risk Governance of the People’s Palm Plantation Partnership Program in Bangka Regency - Shulby Yozar Ariandhy (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2013)
Nowadays, partnership has become one of new forms of governance. It is not effective for the government to handle all public services on its own because the society’s current situation turns to be more complex and complicated. However, there are risks inherent in every partnership. Every party involved in a partnership has each own potential risk. In the context of palm plantation management partnerships, uncertainty in managing risks will lead to a number of conflicts. Thus, it is important to pay attention to risk governance in a partnership. This study aims at describing how the risk governance is done in KKSR (Kebun Kelapa Sawit Rakyat/People’s Palm Plantation) program in Bangka Regency, Indonesia. There are 3 main focuses of this study, namely the process, the strategy and the result of risk governance in KKSR program. The results show that the there are different interests among the parties involved in the partnership which are potential to be the cause of conflicts. Furthermore, the partnership achievement indicates that the strategy of risk governance applied in KKSR Program initiated by the Government of Bangka Regency has given positive impact on each party involved in the partnership. The result of this study also implies the importance of government role in the risk governance process of the partnership program for public services. The government is responsible for protecting the stakeholders’ interests, especially public interests, and also responsible for assuring that the goals of the partnership are achieved.